A Habituation Method in Education Character: an Ibn Miskawaih Thought - Hadi Candra; Pristian Hadi Putra; Yelni Erniyati (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The learning experience of education in Indonesia, as described in the Character Education Master Design document, is built through a habituation approach. Meanwhile, Ibn Miskawaih states that character building is created through habit and practice. The synchronization of both is needed to optimize the implementation of character education in Indonesia today. Habituation in character education is a form of practice that is carried out continuously from the cognitive and practical faculties, which are actualized in behavioral attitudes, by directing them to perfection gradually, based on the thought, until they get used to these behavioral attitudes, then this condition continues until the end of time. In a relatively long time, it becomes a character.